Regenerative Endodontic Procedures: A Perspective from Stem Cell Niche Biology. - Mari-Beffa, Manuel; Segura-Egea, Juan José; Díaz-Cuenca, Aránzazu (Elsevier, 2017)
Introduction: Endodontics uses cell therapy strategies to treat pulpal and periapical diseases. During these therapies, surgeons aim to reconstruct the natural microenvironments that regulate the activity of dental stem cells. Methods: We searched for more than 400 articles in PubMed using key words from regenerative endodontics and dental stem cell biology. In 268 articles, we reviewed what factors may influence histologic results after preclinical dental treatments that use regenerative endodontic procedures after pulpectomy. Results: Several factors, such as the origin of stem cells, the biomimicry of scaffolds used, and the size of lesions, are considered to influence the histologic appearance of the regenerated pulp-dentin complex after treatments. Information is accumulating on transcription factors that generate the pulp-dentin complex and survival/trophic factors that would benefit niche recovery and histologic results. Conclusions: In this article, we discuss the noninterchangeability of stem cells, the influence of dentin-entrapped molecule release on pulp regeneration and survival of stem cells, and the need of positional markers to assess treatments histologically. The ex vivo amplification of appropriate dental stem cells, the search for scaffolds storing the molecular diversity entrapped in the dentin, and the use of positional transcription factors as histologic markers are necessary to improve future preclinical experiments.
Journal of Endodontics
https://openpolicyfinder.jisc.ac.uk/id/publication/13882
Keywords: Endodoncia; Células madre; Investigación científica - Uso terapéutico; Biomaterial; Endodontics; Equivalence; Regenerative endodontic procedures; Stem cell niche; Translational research